Public key system by using isomorphism group - Baghdad Science Journal (مجلة بغداد للعلوم)
In this paper we deal with the problem of ciphering and useful from group isomorphism for construct public key cipher system, Where construction 1-EL- Gamal Algorithm. 2- key- exchange Algorithm